Mechanism for rapid growth of organic–inorganic halide perovskite crystals - Pabitra K. Nayak; David T. Moore; Bernard Wenger; Simantini Nayak; Amir A. Haghighirad; Adam Fineberg; Nakita K. Noel; Obadiah G. Reid; Garry Rumbles; Philipp Kukura; Kylie A. Vincent; Henry J. Snaith (Nature Communications, 2016)
Single crystals of lead halide perovskites exhibit good optoelectronic properties. Here, the authors study and deduce the mechanism for crystallisation and show how controlling dissolution of colloids through varying the acidity and temperature can improve the quality of the single crystals.